Research of the information formation features of the prices at the construction market - SELEZNOVA, Olha; SICHNYI, Serhii; TUZIN, Oksana (Ways to Improve Construction Efficiency, 2025)
The article thoroughly examines the levels of information aggregation of construction market prices providing detailed description and analysis of each level. The distribution of aggregation levels on the markets of construction resources and construction product, as well as the sequence of formation, collection, processing, and dissemination of information on construction prices are graphically illustrated. The characteristics of price information and sources of information are described, namely: the process of data collection, the quality and condition of the source information, and changes in the error and reliability of calculations at different levels of aggregation. It is noted that the higher the level of data aggregation, the greater the probability of obtaining errors in the calculations. The sources of information on construction resources prices and their ownership forms by aggregation levels are presented. It is noted that the qualitative characteristics of the information determine the technological chain required for its acquisition, namely: the method of collecting and processing input data, calculation algorithms, the structure and content of the output information. An approach to determining the reliability error and the predicted cost of construction as key factors in choosing an information source is proposed. It is stated that the error in determining the current market price consists of data sampling error and the calculation delay error at the corresponding aggregation level. An example of determining the calculation accuracy error is provided. It is emphasised that the error in determining the current market price of each resource should be less than the specified accuracy of the price analysis calculation. Furthermore, price analysis should ensure an acceptable and sufficient level of reliability and accuracy at minimal implementation costs. It is concluded that price analysis may also be subject to requirements regarding the timing of price analysis and the cost of price analysis. The features of price analysis at different stages of construction cost planning are presented and analyzed. It is recommended to align the requirements for calculating construction costs in line with the level of detail in design decisions, to specify the requirements for information sources used in price analysis, the structure and content of results, to provide possible data collection algorithms, and to estimate the level of labor costs.